Participative Leadership: Enhancing Overall Personnel Performance Outcomes - Heru Prasetyo; Priyanto Suharto (PT Keberlanjutan Strategis Indonesia, 2026)
Personnel performance plays a very important role for every organization in realizing the work program targets that the organization, including military organizations, has set. This study aims to explore the determination of the Performance of Indonesian Army Military Personnel. In addition, this study examines the relationship between personnel performance influenced by Military Participative Leadership, Organizational Commitment and Remuneration. This research was conducted with a quantitative approach based on primary data. The research sample used was the Indonesian Army Central Executive Agency's Work Unit, with a size of 310 respondents. The statistical tool used in this study is SmartPLS 3. The results show that Military Participative Leadership, Organizational Commitment and Remuneration affect Personnel Performance. Furthermore, Organizational Commitment shows that it can mediate the relationship between Military Participative Leadership and Personal Performance. Furthermore, remuneration has also been shown to moderate the relationship between Military Participative Leadership and Personal Performance.